If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3) + -1(7x + 8) = 35 Reorder the terms: (-3 + 4x) + -1(7x + 8) = 35 Remove parenthesis around (-3 + 4x) -3 + 4x + -1(7x + 8) = 35 Reorder the terms: -3 + 4x + -1(8 + 7x) = 35 -3 + 4x + (8 * -1 + 7x * -1) = 35 -3 + 4x + (-8 + -7x) = 35 Reorder the terms: -3 + -8 + 4x + -7x = 35 Combine like terms: -3 + -8 = -11 -11 + 4x + -7x = 35 Combine like terms: 4x + -7x = -3x -11 + -3x = 35 Solving -11 + -3x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -3x = 35 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 35 + 11 -3x = 35 + 11 Combine like terms: 35 + 11 = 46 -3x = 46 Divide each side by '-3'. x = -15.33333333 Simplifying x = -15.33333333
| 0.65x+0.05(4-x)=0.10(-58) | | 7z+7z=84 | | 2m-5(m-4)=8+m | | 7x-3(x+7)=35 | | 2b+11=15-6b | | 3x+13=-74 | | 8x-5=-5x+5 | | 2x=(3x-2)(m+4) | | 2w+(2w+13)=54 | | 8x-(3x-5)=433 | | 9x^2+4x=12x | | 7+4(t-9)=2(t+6)+5 | | 12s^2+s-35= | | 9=5x+6 | | 4944=48(-32+x) | | x(x-9)+20=0 | | 980=-98p | | p(t)=-3t^2-7t-8 | | x+(x+13)=54 | | x=0.8x+2.8 | | 4a^2-144=0 | | 6p=228 | | 5-x-2=3 | | x=6x+3x | | 10x+6=2x+44 | | 6+4(1+3x)=7(x-5) | | 55=-7x+6 | | -1.4(-4p-1)+4.4p= | | 9y-3=7y+1 | | 4x+7=7(x+1)-3x | | 26-(3x-10)=6 | | 4-36= |